Effect of metabolic syndrome on incidence of oral potentially malignant disorder: a prospective cohort study in Taiwan. Issue 10 (14th October 2020) - Siewchaisakul, Pallop; Wang, Sen-Te; Peng, Szu-Min; Sarakarn, Pongdech; Chen, Li-Sheng; Chen, Tony Hsiu-Hsi; Yeh, Yen-Po; Yen, Amy Ming-Fang
Abstract : Objectives: We aimed to assess the effect of metabolic syndrome (MetS) on incident oral potentially malignant disorder (OPMD). Design: We conducted a prospective cohort study of the Changhua community-based integrated screening (CHCIS) programme and nationwide oral cancer screening programme during the period between 2005 and 2014. Setting: CHCIS, Taiwan. Participants: We enrolled 17 590 participants aged 30 years and older. Main outcomes and measures: We assessed the impact of MetS on the outcome measured by incident OPMD. Results: The incidences of OPMD among subjects with and without MetS were 7.68 ‰ and 5.38 ‰, respectively. After adjusting for confounders, subjects with MetS exhibited a statistically greater risk of developing OPMD compared with those who were free of MetS by 33% (adjusted rate ratio, aRR=1.33, 95% CI 1.14 to 1.55). Individual components of MetS still remained significant, including central obesity (aRR=1.22, 95% CI 1.04 to 1.44), hypertriglyceridaemia (aRR=1.26, 95% CI 1.07 to 1.49) and hyperglycaemia (aRR=1.20, 95% CI 1.02 to 1.41). Central obesity and hypertriglyceridaemia were also statistically associated with a subtype of OPMD, namely, leukoplakia. Conclusion: The temporal influence of MetS on the risk of incident OPMD was noted in our prospective cohort study. Therefore, promoting an MetS prevention and control programme might reduce the occurrence of OPMD and oral cancer.